The effect of suffusion on small strain shear modulus of gap-graded soil under principal stress rotation - Sanjei Chitravel; Masahide Otsubo; Reiko Kuwano (Soils and Foundations)
Internal erosion involves the transport of soil particles from within or beneath a geotechnical structure due to seepage flow, influencing the subsequent mechanical and hydraulic behaviour of the soil. However, predicting changes in small-strain modulus (Gmax) with eroded fines and varying principal stress directions can be challenging due to various factors related to soil fabric. The present study investigates the impact of seepage flow on Gmax, as well as the effect of principal stress rotation (PSR), of gap-graded soil with a fines content of 20%, using a novel erosion hollow cylindrical torsion shear apparatus. The erosion test results indicate that, regardless of density, the Gmax generally increases with seepage time. The trend of Gmax measured in the vertical and torsional directions varies significantly, as seepage is applied always downward, resulting in a different impact on the vertical and horizontal bedding planes. After a cycle of PSR, the induced torsional shear strain is found larger for the eroded specimens, while vertical strain decreases due to fine removal accompanied by seepage flow. In the PSR tests, the specimens subjected to erosion exhibit a greater reduction in Gmax compared to non-eroded specimens, with increasing the angles of principal stress direction. This reduction may be due to the inefficacy of the reinforced soil skeleton established by erosion against shearing. The distribution of fine particles and anisotropy induced by seepage flow contribute to non-trivial mechanical behaviour during principal stress rotation, particularly regarding small-strain shear modulus.